Müller-Weiss disease: the state of the art - Farias Molina, Wellington; Gushiken, Erika; Bottino Martins , Guilherme; Galizia Heitzmann, Lourenço; Pimenta , Luiz Sergio Martins; Fonseca , Elizabeth De Alvarenga Borges da; Macedo, Gustavo Demasi Quadros de (Journal of the Foot & Ankle, 2024)
Müller-Weiss disease generates complex biomechanical changes in the feet, and although it is a rare disease, its true prevalence is not known. In addition to the low population incidence, some cases remain asymptomatic, which contributes to the disease being underdiagnosed or even unknown by the general orthopedist. Its most striking clinical feature results from the combination of paradoxical flatfoot with insidious midfoot pain, resulting in different degrees of difficulty for ambulation and progressive collapse of the plantar arch. Treatment begins with the conservative approach, and surgical treatment is indicated when failure occurs. In this review, we intend to clarify the subject, as misunderstandings or delays in diagnosis negatively impact treatment outcomes by worsening anatomical changes and functional deviations that arise from these issues. There are few studies on this disease, most of them being case series, which highlights the need to concentrate on performing multicenter studies that can collaborate in clarifying the numerous issues involving this deformity. In summary, Müller-Weiss disease is rare and complex, with its etiological characteristics and treatment still lacking consensus in the literature. Due to the absence of validated therapeutic algorithms, we continue to adopt individualized treatment for each foot, tailored to the specific characteristics of each patient. Level of evidence V; Therapeutic studies - investigating the results of treatment; Expert opinion.